Evaluation of marine pigment bacteria-related biological potential research over 9 decades (1933–2023): A bibliometric and visualization analysis - Muhammad Evy Prastiyanto, Afifah Khairunnisa, Rizal Maarif Rukmana, Lia Kusmita, Mutmainah, Muhammad Hizbul Wathon, Sri Darmawati, Kurniawan (Journal of Applied Pharmaceutical Science, 2024)
Marine pigment bacteria have the ability to synthesize a wide range of bioactive chemicals with a variety of industrial and medical applications, they have attracted a lot of attention recently. These bacteria can produce pigments with a variety of biological properties. Researchers have discovered that the pigments made by marine bacteria contain antibacterial, anti-cancer, antiviral, and antioxidant properties that make them desirable for application in a variety of industries. The study aimed to analyze the global profile of literature on pigment marine bacteria. A bibliometric analysis of research papers on marine pigment bacteria that were indexed in the Scopus database between 1933 and 2023 is presented in this article. A total of 955 publications were published worldwide, with an average of 11 documents being produced each year. With 183 documents, the US produced the most, followed by India with 128, China with 116, and Germany with 101. Global publication numbers have been rising consistently since 2007. Antimicrobial activities, bacterial isolation, sequence homology, and marine biology are becoming more important topics for this field’s research on a global scale. The current study offers a distinctive summary of marine pigment bacteria research conducted worldwide from 1933 to 2023, and it can be useful in directing future studies.
Keywords: Marine pigment bacteria, bibliometric, VOSviews, antimicrobial